Survival of Necessity Immigrant Entrepreneurs:: An Exploratory Study - Chrysostome, Elie; Arcand, Sebastien (Journal of Comparative International Management)

(untitled) (None, 2009)
The immigrant entrepreneurs face many obstacles in host countries. Recently some researchers in management and economics have started to shade some light on these issues. However, there still remains much to be known about the phenomenon of immigrant entrepreneurship. The purpose of this paper is to fill this gap. It focuses on the factors that can foster the survival and success of the immigrant entrepreneur. This research studies the factors that can help necessity immigrant entrepreneurs achieve businesses success in their host countries. It proposes a profile for the necessity immigrant entrepreneur and discuss the relevance of the concepts of success and survival for necessity immigrant entrepreneurs. The research proposes a model that is rooted in a theoretical explanation of the survival of immigrant entrepreneurs. This model has been tested through a multiple-case study of immigrant entrepreneurs in the Latin American community of Montreal, Canada, and the results are discussed.